Concise Syntheses of Alternariol, Alternariol-9-monomethyl Ether and Their D3-Isotopologues - Sebald, Michael A.; Gebauer, Julian; Koch, Matthias (Synthesis, 2022)
Alternariol (AOH) and alternariol-9-monomethyl ether (AME) are two secondary metabolites of Alternaria fungi which can be found in various foodstuffs like tomatoes, nuts, and grains. Due to their toxicity and potential mutagenic activity the need for the development of high-throughput methods for the supervision of AOH and AME levels is of increasing interest. As the availability of both native and labeled AOH and AME analytical standards is very limited, we herein present a novel and concise approach towards their synthesis by employing a ruthenium-catalyzed ortho-arylation as the key step. Finally, we demonstrate their suitability as internal standards in stable-isotope dilution assay (SIDA)-HPLC-MS/MS analysis, a technique commonly used for the quantification of natural products in food and feed.
Keywords: homogeneous catalysis; lactones; natural products; ruthenium; total synthesis